Pemalsuan Tanda Tangan Kredit Bank Dalam Pengikatan Hak Jaminan Atas Kebendaan Milik Orang Lain - Syesil Ramaliza Husna; Taupiqqurrahman Taupiqqurrahman (Universitas Widya Gama Malang, 2023)
Civil law is one of the many positive laws that are actively enforced in Indonesia, which is a constitutional state governed by a wide variety of positive laws. What is more often referred to as